2010
DOI: 10.1186/1471-2334-10-312
|View full text |Cite
|
Sign up to set email alerts
|

Secular trend in candidemia and the use of fluconazole in Finland, 2004-2007

Abstract: BackgroundIn a previous study we observed an increasing trend in candidemia in Finland in the 1990s. Our aim was now to investigate further population-based secular trends, as well as outcome, and evaluate the association of fluconazole consumption and prophylaxis policy with the observed findings.MethodsWe analyzed laboratory-based surveillance data on candidemia from the National Infectious Diseases Register during 2004-2007 in Finland. Data on fluconazole consumption, expressed as defined daily doses, DDDs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
81
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 39 publications
(97 reference statements)
16
81
6
Order By: Relevance
“…Potential risk factors associated with candidaemia, such as the previous use of antimicrobial drugs, central lines, the use of corticosteroids, parenteral nutrition and surgery, were also identified in our study (Wey et al 1988, Colombo et al 2006, Sofair et al 2006, St-Germain et al 2008, Poikonen et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential risk factors associated with candidaemia, such as the previous use of antimicrobial drugs, central lines, the use of corticosteroids, parenteral nutrition and surgery, were also identified in our study (Wey et al 1988, Colombo et al 2006, Sofair et al 2006, St-Germain et al 2008, Poikonen et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the incidence rates published by other groups in our country (Colombo et al 2007, França et al 2008, Girão et al 2008, Nucci et al 2010), but consistently higher than studies conducted in the northern hemisphere. Epidemiological studies performed in tertiary care hospitals in Europe and the United States have shown incidence rates ranging from 0.02-1.08 cases per 1,000 hospital admissions (Hajjeh et al 2004, Tortorano et al 2004, Almirante et al 2005, Zilberberg et al 2008, Poikonen et al 2010, Arendrup et al 2011, Das et al 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several populationbased surveys in the United States, Canada, Europe, and Australia have reported an increasing incidence. In the United States, the incidence of candidemia has ranged from 6.0 to 13.3/100,000 population per year (4)(5)(6), whereas, at the same time, the incidence rates in most European countries have been lower, ranging from 1.9 to 4.8/100,000/year (7)(8)(9)(10)(11)(12). Exceptionally high incidence of candidemia has recently been reported both in Baltimore, 26.2/ 100,000/year (4), and Denmark, 8.6/100,000/year (13).…”
mentioning
confidence: 99%
“…However, significant geographical differences in species distribution exist. The proportion of candidemia caused by C. albicans ranges from 37% in Latin America up to 70% in the Nordic countries (10,11,14). Furthermore, the relative proportions of non-albicans Candida pathogens also vary between the northern and southern parts of the world.…”
mentioning
confidence: 99%